Kontruksi Makna Kesabaran dalam Kehidupan Remaja Muslim: Pendekatan Grounded Theory Perspektif Hadis - Gunawan Al-Faridjahal; Muhammad Alif; Repa Hudan Lisalam (Al-Hasyimi: Jurnal Ilmu Hadis, 2025)
Patience is a fundamental value in Islamic teachings that is reflected in many traditions of the Prophet Muhammad. However, how Muslim adolescents interpret patience in the context of daily life is an interesting issue to be studied in more depth. This article aims to build a theoretical understanding of the construction of the meaning of patience in the lives of Muslim adolescents through Kathy Charmaz's constructivist Grounded Theory approach, combined with an analysis of the hadiths related to patience. This study was conducted by examining the real experiences of Muslim adolescents in various social and spiritual contexts, such as academic pressure, emotional conflicts, and the search for Islamic identity. Data were collected through contextual literature review, phenomenological observation in digital social spaces and Islamic communities, as well as reflection on daily narratives spread in social media and the work of Muslim teenagers. All findings were analyzed using the principles of open coding and theoretical coding typical of Grounded Theory. The results show that patience is not only understood as a passive attitude of restraint, but is interpreted as an active struggle in maintaining values, strengthening faith, and building resilience. This understanding is shaped by the interaction between the hadith teachings, the collective experiences of adolescents, and the values that develop in their social environment. This article emphasizes the importance of a contextual approach in understanding Islamic values that live in the reality of adolescents, and encourages the development of character education based on spirituality and culture of the younger generation.